Understanding Judaism and the Jews in the Gospel of John polemic, tradition, and Johannine self-identity - Thiel, Nathan 1986- (Lanham Boulder New York London Lexington Books/Fortress Academic, 2024)
"This book shows how the Fourth Gospel's language about "the Jews" is profoundly shaped by its scriptural imagination. It is the product of a self-consciously Jewish author who saw himself as living and writing from within the Jewish tradition"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Jews in the New Testament; Christianity and other religions -- Judaism